Improving the Law Office: Principles for Design - (:unkn) unknown (My University, 1989)
This report describes an applied research, translation and design application project. Information about the law offices was gathered and transformed into fifteen critical design principles. The format and approach leading to design principles creates powerful descriptions of the organizational and individual needs that will affect law office facility design. Seventeen different solutions to a program for a 267 person Chicago law firm are used to illustrate the application of the design principles.
Keywords: Law Offices